Fixed comparisons with zoonym component describing human qualities - Аzharbekova, A.N.; Bakhtikereyeva, U.М. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article considers the fixed comparisons describing human qualities and their emotional-expressive meaning. The object of the research is fixed comparisons with zoonym component that describe human qualities. The use of animal names in Turkic languages, their associative image in national perception was analyzed by comparative method. Based on scientific findings on associative types of fixed comparisons during language analysis, the fixed comparisons of human characteristics are classified into associative types. Associations that appear by means of the images of a wolf, a lion, a tiger, a fox, a bear, a hare in Kazakh perception are analyzed. The role of comparative components in using emotional-expressive meaning of fixed comparisons is defined. Comparisons describing qualities of heroism, courage, cowardice, weakness, beauty are divided into functional emotional-expressive comparisons and attributive emotional-expressive comparisons by their emotional- expressive meanings. It is proved that heroism, courage qualities are given by the images of a wolf, a lion and a tiger, severity, cruelty is expressed by a wolf’s image, quality of cowardice is depicted by the image of a hare, cunning, disingenuity, beauty are given by the image of a fox. The importance of fixed comparisons with zoonym component in describing the level of expressiveness and artistry in human qualities in the use of language are defined.
Адами қасиеттерді бейнелейтін зооним компонентті тұрақты теңеулер
Устойчивые сравнения с компонентом-зоонимом, характеризующие человеческие качества
Keywords: fixed comparisons; associative type; functional emotional-expressive type; attributive emotionalexpressive type; positive; negative emotions; animal names with emotional-expressive meaning: lion, tiger; wolf; fox; rabbit; human qualities: heroism; cowardice; cunning; weakness; cruelty; beauty